Epidemiological Study of Hepatitis B, C and HIV Cases among the Foreigners Visiting Sulaimani City from 2013 Through 2016 - Omer Mohammed, Mohammed; Baram Hasan, Asan; Bakir Maarouf, Fenk (Kurdistan Journal of Applied Research, 2019)
Hepatitis B, C and HIV infections present a great public health problem worldwide. More than 350 million of world's populations have chronic HBV infection and near 1 million people are dying due to this infection each year. About 150-200 million of world's population have chronic HCV infection that leads to nearly 350 000 deaths annually. On the other hand HIV remains as a major global public health issue. In 2015, about 36.7 million people were living with HIV and 1.1 million people died of HIV related illnesses.To find the prevalence of HB, HCV and HIV infection among the foreigners who visited Sulaimani city in 2013 through 2016 and evaluate the common risk factors in those who had a positive results in 2016. This study was conducted between 1stof January 2016 and 31st December 2016. A total number of 275,979 foreigners who were referred formally to the central laboratory- residency department in Sulaimani city for screening for (HBsAg, HCV Ab and HIV Ab) from 2013 through 2016 were analyzed and all the foreigners who visited Sulaimani city in 2016 were included with assessment of demographic data and risk factors among the positive cases. Among 275,979 foreigners who visited Sulaimani city from 2013 through 2016, theoverall prevalence of HBV infection was0.47%(1318 cases), HCV 0.01 %( 267 cases) and HIV 0.01 %( 30 cases). In 2016 the highest prevalence of HBV infection was among Syrians which was 2.5% while highest HCV prevalence was among Europeans 0.82%. Ages of the patients ranged between (18-65) years, 85.4% were males, 65.2% of males and 45.7% of females were married. Dental procedures, surgery, blood transfusion and family history were common risk factors.HBV infection was highest among Syrian foreigners. While the highest HCV prevalence was among Europeans. An immediate action plan is needed to screen all Syrian refugees in our region for HBV, HCV and HIV to determine active infection and treat accordingly and also impose preventive measures to halt the spread of the infections.